2016
DOI: 10.1186/s40781-016-0101-9
|View full text |Cite|
|
Sign up to set email alerts
|

Dry aging of beef; Review

Abstract: The present review has mainly focused on the specific parameters including aging (aging days, temperature, relative humidity, and air flow), eating quality (flavor, tenderness and juiciness), microbiological quality and economic (shrinkage, retail yields and cost) involved beef dry aging process. Dry aging is the process where beef carcasses or primal cuts are hanged and aged for 28 to 55 d under controlling environment conditions in a refrigerated room with 0° to 4 °C and with relative humidity of 75 to 80 %.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
173
3
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(211 citation statements)
references
References 26 publications
9
173
3
26
Order By: Relevance
“…Savell reported that many of the compounds responsible for flavor are concentrated by the dry-aging process [12]. Namely, the distinguishing effect of the dry-aging process on beef is that it concentrates the flavor [4, 12, 17]. Contrary to expectation, the present result didn’t show that free amino acids concentrate during the aging process as reported above.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Savell reported that many of the compounds responsible for flavor are concentrated by the dry-aging process [12]. Namely, the distinguishing effect of the dry-aging process on beef is that it concentrates the flavor [4, 12, 17]. Contrary to expectation, the present result didn’t show that free amino acids concentrate during the aging process as reported above.…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, the increased interest in dry-aged beef has emerged not only in Western countries but also in Asian countries such as South Korea, Japan, Singapore, Taiwan, and Hong Kong [4]. In Okinawa, new businesses related to the dry-aging of beef have been opened.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations